2008
DOI: 10.1111/j.1365-2109.2008.01924.x
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the culture of the Mexican bullseye puffer fish Sphoeroides annulatus, Jenyns (1842)

Abstract: This paper provides a brief description of the natural history known of the genus Sphoeroides as an introduction to the biology of Mexican puffer fish Sphoeroides annulatus Jenyns (1842). Studies to determine the culture potential of this species during 11 years are described. At the experimental level, useful advances have been made on S. annulatus and reproductive and rearing husbandry practices together with the nutritional requirement, physiological studies, diseases and control therapies are discussed. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 42 publications
0
18
0
1
Order By: Relevance
“…Sphoeroides annulatus is an economically important fish; it is both a highly appreciated food in the region and exported in large quantities. Biotechnological research has revealed that S. annulatus has a good potential for aquaculture in Mexico (Chávez-Sánchez et al 2008). We consider that more information about the biology of L. simplex is required.…”
mentioning
confidence: 99%
“…Sphoeroides annulatus is an economically important fish; it is both a highly appreciated food in the region and exported in large quantities. Biotechnological research has revealed that S. annulatus has a good potential for aquaculture in Mexico (Chávez-Sánchez et al 2008). We consider that more information about the biology of L. simplex is required.…”
mentioning
confidence: 99%
“…The puffer fish Sphoeroides annulatus (Jenyns, 1842) is a common species in marine and coastal waters of the eastern Pacific from southern California to Peru, including the Gulf of California (Bussing, 1995;Amezcua-Linares, 1996), which has become a target species for the artisanal fishing fleets of the Mexican NW, for its high market price due to the quality of its meat (Chávez-Sánchez et al, 2008;Aguilera & Duncan, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…In this latter sense there is a controversy about the toxicity of S. nephelus, because some studies mention that their meat is safe to consume by humans (Burklew and Morton 1971), while recent studies has identified a certain degree of toxicity related to regional variations , Deeds et al 2008, Abbott et al 2009) and may be harmful to humans. However, in other puffer species, it has been observed that their toxicity may be considerably reduced when pufferfishes are grown in controlled systems and make them suitable for human consumption (Noguchi et al 2006, Chávez Sánchez et al 2008, Arakawa et al 2010). This latter approach would represent a possible opportunity for further studies whose aim would be to explore whether toxicity in S. nephelus is reduced in captivity and then the specimens are reared to suitable sizes for consumption.…”
Section: Discussionmentioning
confidence: 99%
“…In India, the use of pufferfish liver oil as a source of barbitone is being investigated (Mitra et al 1989, Ghosh et al 2005). In addition, since it has been observed that their toxicity is considerably reduced when pufferfish are grown in controlled systems, some of these species are known as suitable for human consumption and thus receive good acceptance in Asian markets (Noguchi et al 2006, Chávez Sánchez et al 2008, Arakawa et al 2010. Particularly, the genus Sphoeroides represents an important source of protein in different parts of the world.…”
Section: Introductionmentioning
confidence: 99%